An empirical approach to marketing innovation in small and medium retailers: An application to the Spanish sector - Natalia Medrano; Cristina Olarte-Pascual (Contemporary Economics, 2016)
Although numerous studies explore innovation, most of them focus on technological innovations. It is currently difficult to focus exclusively on products and processes when discussing innovation because new ideas can transform any part of an organization's value chain. Indeed, marketing innovation is essential for small and medium firms and its study is extremely important given the current lack of empirical evidence. Furthermore, the retail sector in Spain plays a significant role in the country's economy due to its contribution to gross domestic product and employment and to its role in the growth of cities and regions. In this context, the present study analyzes the determinants of marketing innovation practices of small and medium retailers and the relationships among the four types of innovation (product, process, organizational and marketing) to improve our understanding of marketing innovations in the retail sector. This study uses secondary data on innovation activity for Spanish companies in the years 2010-2012. Logistic regression models are estimated, and the results show that the introduction of new marketing methods has a positive impact on the propensity to engage in all other types of innovation (product, process and organizational). Furthermore, all of these methods positively impact the propensity to introduce marketing innovations. This study concludes with insights that can help managers to direct innovation processes in their companies and assist public administrators in the promotion of marketing innovations among small and medium retailers.
Keywords: M31; O32; 330; marketing innovation; non-technological innovations; retail; SME